The most controversial decision Truman, the atomic bombs, and the defeat of Japan - Miscamble, Wilson D. 1953- (New York Cambridge University Press, 2011)
"This book explores the American use of atomic bombs, and the role these weapons played in the defeat of the Japanese Empire in World War II. It focuses on President Harry S. Truman's decision making regarding this most controversial of all his decisions. The book relies on notable archival research, and the best and most recent scholarship on the subject to fashion an incisive overview that is fair and forceful in its judgments. This study addresses a subject that has been much debated among historians, and it confronts head-on the highly disputed claim that the Truman administration practiced atomic diplomacy. The book goes beyond its central historical analysis to ask whether it was morally right for the United States to use these terrible weapons against Hiroshima and Nagasaki. It also provides a balanced evaluation of the relationship between atomic weapons and the origins of the Cold War"--Provided by publisher.
Introduction: the most controversial decision -- Franklin Roosevelt, the Manhattan Project, and the development of the atomic bomb -- Harry Truman, Henry Stimson, and atomic briefings -- James F. Byrnes, the atomic bomb, and the Pacific War -- The Potsdam Conference, the Trinity test, and 'atomic diplomacy' -- Hiroshima, the Japanese, and the Soviets -- The Japanese surrender -- Necessary, but was It right? -- Byrnes, the Soviets, and the American atomic monopoly -- The atomic bomb and the origins of the Cold War.
Includes bibliographical references and index.
AC-12771d donated by Japan Foundation
Keywords: Truman, Harry S. -- 1884-1972 -- Military leadership; Atomic bomb -- History; Atomic bomb -- Moral and ethical aspects; Hiroshima-shi (Japan) -- History -- Bombardment, 1945 -- Moral and ethical aspects; Nagasaki-shi (Japan) -- History -- Bombardment, 1945 -- Moral and ethical aspects; United States -- Military policy -- Decision making